The summer Hikaru died. 6 - Mokumokuren (Yen Press, 2025)
"At last, Yoshiki and 'Hikaru' have their explanation for what 'Hikaru' isn't, what he is, and what his fate may be. Tanaka may have all the answers, but he also needs their help. 'Hikaru' isn't the only entity that has reached over from the other side, and without intervention, the holes between worlds could grow beyond Tanaka's ability to close them. Head, arms, legs--will Yoshiki and 'Hikaru' still have them all when their task is done?"--